Quality of cookies with partial substitution of wheat flour for okra flour - Xavier, Swan Nunes; Silva, Alvaro Gustavo Ferreira da; Souza, Pahlevi Augusto de; Sales, Giuliana Naiara Barros; Costa, Franciscleudo Bezerra da; Ribeiro, Wellington Souto (Comunicata Scientiae, 2022)
Okra is a vegetable of high nutritional value, but highly perishable when stored in natura. Cookies are products of great popular acceptance and allow the use of alternative flours. The objective was to evaluate cookies made with partial substitution of wheat flour for okra. Okra fruits were dried to obtain the flour. This was applied in biscuit formulations at concentrations of 0 (A), 5 (B), 10 (C) and 15% (D). The cookies were evaluated for the difference in mass, thermal factor, yield, humidity, ash, fibers, proteins, lipids, carbohydrates, caloric value, presence of Coliforms at 45 ° C, positive coagulase Staphylococcus and Samonella sp., In addition to the sensory evaluation acceptance and purchase intention. The dough, ash content, fiber and protein of the cookies enriched with okra flour were higher. The carbohydrate content and caloric value was higher in formulation A. All cookies are within the microbiological standards required by law. Sensory acceptance and purchase intention were superior in formulations A and B. The differences between the cookies are due to the different composition of the okra and vary according to the concentration in which it is added. Formulation B obtained better nutritional quality without interfering with its good sensory acceptance.